Community structured production of zooplankton in the eastern boundary upwelling system off central/southern Chile (2003–2012). (4th November 2019) - Medellín-Mora, Johanna; Atkinson, Angus; Escribano, Rubén
Abstract: Eastern boundary upwelling systems (EBUS) are highly productive and climatically sensitive ecosystems of the ocean. A critical component sustaining EBUS is the zooplankton secondary production (ZSP) which links primary production (PP) and the higher trophic levels. However, estimating ZSP is a complex task and many questions remain regarding its controlling factors. Here, we used automated analysis to assess taxonomic-structured biomass of zooplankton from a time series (2003–2012) at a fixed station off central-southern Chile. Zooplankton biomasses combined with empirically estimated growth rates, as a function of temperature, Chorophyll-a concentration, and body size, were used to estimate seasonal and interannual changes in ZSP. The annual integrated ZSP yielded a mean of 8.0 g C m −2 y −1, with a minimum in 2009 of 5.7 g C m −2 y −1 and a maximum in 2011 of 13 g C m −2 y −1, and an average annual P/B ratio of 35. The transfer efficiency from PP to ZSP was only 0.8%, indicating a surplus of PP to the system and/or the importance of intermediate microzooplankton levels. Seasonal variation in biomass, ZSP and the P/B ratio were explained mostly by changes in taxonomic structure while interannual variation reflected large-scale climatic changes, such as the Pacific decadal oscillation.